HIV seroconversion in the third trimester of pregnancy: using raltegravir to prevent mother-to-child transmission. (March 2013) - Hegazi, A; Hay, P
We describe a case of acute HIV infection in the third trimester of pregnancy associated with an extremely high viral load and the use of raltegravir to prevent HIV mother-to-child transmission.